1999
DOI: 10.1159/000017396
|View full text |Cite
|
Sign up to set email alerts
|

Age and Etiology as Predictors of Language Outcome following Hemispherectomy

Abstract: We report on the effects of etiology and age on the linguistic outcomes in a large pediatric hemispherectomy population. Four populations were considered separately: cortical dysplasia (multilobar involvement), Rasmussen’s encephalitis, infarction as a primary etiology and, fourth, children who failed to develop language, regardless of etiology. We argue against the ‘the-earlier-the-better’ hypothesis and propose our own hypothesis that weds maturational factors to etiological factors to predict language outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
4
6
0
Order By: Relevance
“…We found a significant increase in LQ in patients with shorter duration of epilepsy (p = 0.004). Other reports have previously found that a shorter period of overt seizures might be positive for better general developmental progress [2,12,24,27], which also holds true for language abilities [8,9,16]. Additionally, our results corroborate the finding that children who were off medication after surgery showed significantly better language outcomes (p = 0.003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found a significant increase in LQ in patients with shorter duration of epilepsy (p = 0.004). Other reports have previously found that a shorter period of overt seizures might be positive for better general developmental progress [2,12,24,27], which also holds true for language abilities [8,9,16]. Additionally, our results corroborate the finding that children who were off medication after surgery showed significantly better language outcomes (p = 0.003).…”
Section: Discussionsupporting
confidence: 89%
“…However, most reports published so far on language outcomes following hemispheric surgery have concentrated on anatomic hemispherectomy [8][9][10]21,22,31,35]. These studies concluded that seizure freedom [8][9][10]16] may be a favourable predictor whereas developmental pathologies may be linked with unfavourable language outcomes. The effects of functional hemispherotomy on development have been less extensively studied and the results are inconsistent [1,24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In what we had termed the ''Critical Impact Point'' hypothesis, we proposed that the point in both neurological and functional maturation at which the insult is suffered will determine the subsequent outcome (Curtiss & de Bode, 1999). Our current results refine this hypothesis in that we have found that the variable of etiology, itself, turns out to be the umbrella construct for age, extent, and the mechanism of injury.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, although both formal test performance and language samples were used to evaluate language performance, it was for the analysis of the spontaneous speech samples that GCS was developed. Aspects of this research may be reviewed in Caplan, Curtiss, Chugani, and Vinters (1996), Curtiss and de Bode (1998, 1999a, 1999b, 2003, Curtiss, de Bode, and Mathern (2001), Curtiss and Schaeffer (1997a, 1997b), de Bode (1998), and de Bode and Curtiss (1999.…”
Section: Gcs's Development Contextmentioning
confidence: 99%